Hubungan Lingkungan Kampus Poli-Etnis Dengan Kemampuan Adaptasi dan Komunikasi Mahasiswa Angkatan 2022 Universitas PGRI Pontianak - Indri Oktaviani viani; Adhitya Prihadi; Agus Suwarno (LPD Universitas PGRI Pontianak, 2026)
Abstract: This study aims to examine the relationship between a poly-ethnic campus environment and the adaptation and communication abilities of the 2022 student cohort at PGRI Pontianak University. The study is grounded in the campus's multicultural composition, which creates complex social dynamics that may influence students' adaptation processes and interpersonal communication. A quantitative correlational method was employed using proportionate stratified random sampling. A sample of 280 students from 11 academic programs was selected using the Slovin formula with a 5% margin of error. Data were collected through a four-point Likert scale questionnaire and analyzed using Pearson Product Moment correlation and coefficient of determination (R²). The results indicate that the poly-ethnic campus environment has a positive and significant relationship with students' adaptation ability (r = 0.600; p = 0.000), contributing 36.0%, and with students' communication ability (r = 0.590; p = 0.000), contributing 34.8%. These findings confirm that the more conducive the poly-ethnic campus environment, the better students' adaptation and communication abilities. Keywords: poly-ethnic campus environment, adaptation ability, communication ability, university students